The impact of the European Convention on Human Rights and the European Court of Human Rights in the enforcement of administrative judgments in relation to the Republic of Croatia - Malenica, Ivan (Pravnik, 2025)
The author addresses the enforcement of court judgments, mostly in the light of the European Convention on Human Rights and the European Court of Human Rights. The article provides an analysis of the enforcement of court decisions in the practice of the European Court of Human Rights through established violations of the Convention on Human Rights. The methodology of this research is to analyse the practice of the European Court of Human Rights, which, in many of its decisions, determines the obligation of the state to provide an effective legal remedy for the enforcement of judgments of its courts. The main hypothesis of this research is that effective judicial protection of individuals depends on an effective system of enforcement of court decisions and that it is the obligation of the state to provide an effective legal remedy for the enforcement of court decisions. In this context, the new Croatian Administrative Disputes Act of 2024 and the regulation of the enforcement of administrative court decisions are also being analysed.
Keywords: administrative courts; enforcement; European Convention on Human Rights; European Court of Human Rights; Evropska konvencija o človekovih pravicah; Evropsko sodišče za človekove pravice; izvršitev; upravna sodišča